Comparison of cavitation erosion of NiCrBSi and AISI 316L coatings deposited by powder plasma transferred Arc welding - Weronika Henzler; Mirosław Szala; Tomasz Pałka; Bernard Wyględacz; Artur Czupryński; Leszek Łatka (Acta Polytechnica, 2025)
This study carefully compares the effect of microstructure and hardness on the cavitation wear resistance of PPTA (Powder Plasma Transferred Arc) deposited coatings. Deposits were made on a substrate of S235JR structural steel. Two types of feedstock powder were used: material with the chemical composition of AISI 316L stainless steel, and a nickel-based, self-fluxing powder type NiCrBSi. This study involved conducting cavitation erosion tests on a vibratory test rig in accordance with the ASTM G32 standard, using the stationary specimen method. Metallographic investigations confirmed the presence of austenitic dendrites and delta ferrite precipitations in the microstructure of AISI 316L and the presence of hard carbides and borides within the nickel-based matrix of NiCrBSi hardfacing. It can be seen that the AISI 316L coating, having a much lower hardness in the range of 250–280 HV1, achieved four times poorer cavitation erosion resistance compared to the NiCrBSi coating, which has a hardness in the range of 820–890 HV1. Following the erosion testing, the AISI 316L stainless steel exhibited a mean depth of erosion of MDE6h = 28.8 μm, whereas the NiCrBSi hardfacing exhibited a mean depth of erosion of MDE6h = 7.1 μm. Moreover, NiCrBSi hardfacing exhibits a higher cavitation erosion resistance than the stainless steel coating, with erosion rates of 2.59 mgh−1 (1.60 μmh−1) and 8.11 mgh−1 (5.28 μmh−1), respectively. In the case of different types of overlay material, such as stainless steel and NiCrBSi coatings, the higher hardness and fine, hard particle-rich microstructure improves the cavitation erosion resistance of PPTA overlays.